Time-Resolved Fluorescence of Water-Soluble Pyridinium Salt: Sensitive Detection of the Conformational Changes of Bovine Serum Albumin. Issue 10 (October 2016) - Li, Lei; Yi, Hua; Jia, Menghui; Chang, Mengfang; Zhou, Zhongneng; Zhang, Sanjun; Pan, Haifeng; Chen, Yan; Chen, Jinquan; Xu, Jianhua
In this paper, we report a pyridinium salt "turn-on" fluorescent probe, 4-[2-(4-Dimethylamino-phenyl)-vinyl]-1-methylpyridinium iodide (p-DASPMI), and applied its time-resolved fluorescence (TRF) to monitor the protein conformational changes. Both the fluorescence lifetime and quantum yield (QY) of p-DASPMI were increased about two orders of magnitude after binding to the protein bovine serum albumin (BSA). The free p-DASPMI in solution presents an ultrashort fluorescence lifetime (12.4 ps), thus it does not interfere the detection of bound p-DASPMI which has nanosecond fluorescence lifetime. Decay-associated spectra (DAS) show that p-DASPMI molecules bind to subdomains IIA and IIIA of BSA. The TRF decay profiles of p-DASPMI can be described by the multi-exponential decay function (∑ α n exp ( - t / τ n ) ), and the obtained parameters, such as lifetimes (τ n ), fractional amplitudes (α n ), and fractional intensities (α n τ n ), may be used to deduce the conformational changes of BSA. The pH and Cu 2+ induced conformational changes of BSA were investigated through the TRF of p-DASPMI. The results show that the p-DASPMI is a candidate fluorescent probe in studying the conformational changes of proteins through TRF spectroscopy and microscopy in the visible range.